LOGO-TEKNIK IKLAN NAN CITRA NEGATIF - Sihabul Millah (Universitas Islam Negeri Sunan Kalijaga Yogyakarta, 2014)
This paper studies various kinds of ads that attract women as target. Using Rollan Bartrès’s model of analysis, the results showed that the logo-techniquesin advertising work well to raise the basic human instincts, such as the instincts of intimacy, sex, fear, and the idols that has strong effect to women.